WORKSHOP MODEL BLENDED LEARNING BERBASIS WHATSAPP MENINGKATKAN KOMPETENSI GURU MELAKSANAKAN BDR - Sujarwo Sujarwo (Universitas Ngudi Waluyo, 2021)
The Corona Virus-19 pandemic makes the implementation of learning carried out with learning activities from home. Transition of the learning process from face-to-face to online. The results of observations of the implementation of learning from home at SDN 2 Kesambi, the teacher has not maximally used various online learning resources, which are combined with a learning model that supports learning activities from home. The purpose of this study was to determine the increase in the professional competence of SDN 2 Kesambi teachers in carrying out learning activities from home (BDR). The research used a whatsapp-based blended learning workshop. The results of data analysis showed an increase in teacher competence in carrying out learning, in the initial conditions 82% of teacher competence was in the sufficient category. After being given action in the form of whatsapp-based blended learning workshop activities, the competence of teachers increased in the first cycle to 55% of teachers in good categories and 45% of teachers in sufficient categories, and in cycle II to 10 teachers (91%) who attended workshops in good categories, and 1 teacher (9%) in the sufficient category.